Nursing Interpersonal Communication Model for Schizophrenia Patients at Tampan Mental Hospital Pekanbaru - Novi Dini Restia ,; Lailanisa Fadlilani,; Nurul Mustaqimmah , (JIM - Journal International Multidisciplinary, 2024)
Schizophrenia is a neurological disorder and a serious type of mental illness that affects the patient's perception, thinking, language, emotions, and social behavior. Communicating with individuals suffering from schizophrenia requires special techniques because they tend to experience self-concept issues, immerse themselves in their own world, and exhibit physical well-being but mental unhealthiness. Effective communication with schizophrenia patients necessitates skilled nursing techniques and the ability to communicate effectively. From the perspective of communication science, the relationship between the nurse and the patient falls under interpersonal communication, or from the standpoint of health communication, it is therapeutic communication. The communication between the nurse and the patient creates interpersonal interaction using linguistic symbol systems, such as verbal and nonverbal systems. This study aims to describe and analyze interpersonal communication between nurses and Schizophrenia patients at Rumah Sakit Jiwa in the Riau Province. The research utilizes a case study method. The results show that the interpersonal communication used by nurses with schizophrenia patients at Tampan Mental Hospital in the Riau Province involves empathy, positive attention, and sincere acceptance demonstrated through both verbal and nonverbal forms. This fosters trust and openness in patients towards nurses, ultimately contributing to the improvement of schizophrenia patients' healing process.